Pulmonary stenosis in two female dogs: Case report (Research, Society and Development, 2021)
Pulmonary stenosis is a congenital disease that causes partial obstruction of blood flow between the right ventricle and the pulmonary artery and is found mainly in young and male animals. This work reports the cases of two female dogs of the German Spitz and Yorkshire Terrier breeds, aged 8 months and 9 years respectively. The animals were submitted to lateral and ventrodorsal chest X-rays, which showed right cardiac enlargement and dilation of the pulmonary artery trunk. They were also submitted to an echocardiographic examination that demonstrated pulmonary valves with altered function and morphology and post-stenotic dilation with increased velocity flow, as well as turbulent in the region of this valve. After diagnosis, clinical treatment was established with the use of vasodilators, diuretics, phosphodiesterase inhibitor and β-blocker depending on the needs of each animal, with periodic clinical evaluation of patients and complementary exams to monitor cases being recommended. The established treatment proved to be satisfactory, due to the improvement of clinical signs.